Model pengembangan kurikulum pendidikan agama Islam dalam pendidikan dasar - Ajir, Ikhtiar Cahya; Pahrudin, Agus; Jatmiko, Agus; Koderi, Koderi (Program Studi Pendidikan Agama Islam STAI Auliaurrasyidin Tembilahan, 2024)
The Islamic Religious Education (PAI) curriculum in elementary schools faces various challenges, primarily due to its overemphasis on the cognitive aspect, which is no longer aligned with contemporary needs. This study employs literature review, policy analysis, and empirical research methods to develop a relevant PAI curriculum model. The proposed model emphasizes the integration of Islamic values into learning activities to shape students' character, morality, and spiritual values. The findings indicate that an Islamic value-based, adaptive, and contextual curriculum can enhance students' understanding of religious teachings and strengthen their application in daily life. The curriculum development process highlights the importance of collaboration among educators, parents, and policymakers to create a dynamic curriculum focused on holistic Islamic character development.